BIOCOMATIBLE COPOLYMER FROM CHITOSAN-SUBSTITUTED POLYANILINE: GRAFT COPOLYMERIZATION OF POLY (ORTHOPHENYLE DIAMINE) ONTO CHITOSAN - PRADYUMNA KUMAR SWAIN,; MIRA DASH,; P.L. NAYAK, (International Journal of Pharma and Bio Sciences, 2015)
Chitosan, a natural polysaccharide was grafted with poly (Orthophenylene diamine) through radical copolymerization using ammonium persulfate as the initiator in acidic medium. The chitosan– poly (orthophenylenediamine) was characterized using FTIR, Scanning Electron Microscopy, TGA and UV-visible spectroscopy taking chitosan as reference. Chitosan exhibited electrical conductivity, which increases with the extent of grafting onto chitosan. The application of conducting biomaterial such as Chitosan in the electronic devices especially for the fabrication of sensor devices would be attractive not only in terms of product cost and environmental safety but also from a materials science point of view. A plausible mechanism for grafting has been suggested.